Setting the voting agenda for multi-option referendums: process variations and civic empowerment. Issue 2 (17th February 2021) - Wagenaar, Charlotte C. L.; Hendriks, Frank
ABSTRACT: Referendums figure prominently in discussions about democracy and democratic innovation. Whereas much of the literature is focused on binary versions of the referendum, this article centralizes the non-binary or multi-option referendum, paying special attention to its modalities and the leverage they give to citizens in the ballot agenda-setting stage. Studying agenda-setting in multi-option referendums contributes to our understanding of civic democratic empowerment. For this purpose, we distil from practical experience the process steps and actors involved in triggering multi-option referendums and formulating ballot options. We map them in six main models of agenda-setting processes, three of which are legally institutionalized and triggered through bottom-up processes, allowing for competing proposals by citizens and legislators; three other models are characterized by top-down, ad hoc triggering and entail variation in the involvement of political parties, experts, societal groups and citizens in suggesting or selecting ballot options. Our procedural typology ultimately contributes to the body of research on referendum triggering and option formulation in the context of democratic innovation.